The effectiveness of early anticoagulant treatment in Covid-19 patients. (June 2021) - Arslan, Yakup; Yilmaz, Gulden; Dogan, Deniz; Hasirci, Mine; Cetindogan, Hatice; Ocal, Nesrin; Savasci, Umit; Fidan, Gonca; Tasci, Canturk
Objectives: Coronavirus disease 2019 (Covid-19) is an emerging, fast-spreading and worldwide infectious disease that would be deteriorated with the precipitation of systemic or local thrombosis. The aim of current study was evaluating the effects of early anticoagulant treatment in hospitalized Covid-19 patients. Method: The present retrospective and comparative cohort study investigated 413 hospitalized Covid-19 patients treated with or without Low Molecular Weight Heparin (LMWH) (n = 187 and 226, respectively) in the Covid Clinics of Gulhane Education and Research Hospital in Ankara, Turkey, between March 18 and May 03, 2020. The treatment groups were consisted of the patients evaluated before and after The Covid-19 Treatment Guide update on April 12, 2020 that included the anticoagulant treatment thereafter. Results: The mean age of all 413 patients (204 male and 209 female) at disease onset was 50.6 ± 16.7 years. The LMWH-treated patients had significantly higher coagulation markers such as d-dimer and platelet count than LMWH-untreated patients (p values < 0.05). The inflammatory markers, ferritin, interleukin-6 and procalcitonin were significantly increased in LMWH-untreated patients (p values < 0.05). The presence of any comorbidity was significantly more common in LMWH-treated patients compared to LMWH-untreated group (39.6% vs 19.9%, respectively; p < 0.001). Hypertension and diabetes mellitus were the most frequent comorbidities in both groups. The number of intensive care unit (ICU) transfer and longer length of hospital stay were more commonly observed in LMWH-untreated patients (p values <0.05). Conclusions: Early anticoagulant treatment with relatively higher doses of LMWH may improve the clinical outcome of Covid-19 patients and shorten the length of hospital stay.